2017
DOI: 10.4172/neuropsychiatry.1000172
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation in medical students

Abstract: Suicidal ideation in young adults is an increasingly burdensome issue worldwide. Further, previous research has shown a very high prevalence of suicidal ideation in medical students, ranging from 9.1% to 48.2%. Many factors have been identified as likely contributors to the development of suicidal tendencies in this specific population including certain behavioral and personality traits, co-existing mental health problems, and stressful personal or academic events. In addition, female medical students have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
1
11
0
7
Order By: Relevance
“…So far, there has been no study that has explored the relationship between anhedonia, type D personality and suicidal ideations. Several programs have been developed for medical students with the aim to improve their well-being, to detect untreated and potentially suicidal students anonymously and to increase mental health services utilization [3, 31]. Taking into account the results of the present study it could potentially be helpful to incorporate the anhedonia subscale of the BDI-II and the type D personality scale in future suicide prevention programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, there has been no study that has explored the relationship between anhedonia, type D personality and suicidal ideations. Several programs have been developed for medical students with the aim to improve their well-being, to detect untreated and potentially suicidal students anonymously and to increase mental health services utilization [3, 31]. Taking into account the results of the present study it could potentially be helpful to incorporate the anhedonia subscale of the BDI-II and the type D personality scale in future suicide prevention programs.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors contribute to the development of suicidal ideation in this population. Among these factors, high rates of burnout, depression and certain personality traits (neuroticism, low self-esteem…) have been described [3].…”
Section: Introductionmentioning
confidence: 99%
“…One of the continuous major concerns of researchers is the development of burnout during the time in medical school (e.g., Dahlin and Runeson, 2007;Dyrbye and Shanafelt, 2016), which is associated with several consequences affecting health, such as alcohol abuse (Jackson et al, 2016) and suicidal ideation (Dyrbye et al, 2008;Kosik et al, 2017). According to Dyrbye et al (2014), 56% of medical students experienced symptoms of burnout and over 11% reported suicidal thoughts (Rotenstein et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, suicidal ideation among first year medical students found 31.3% which is considerably higher, but it gradually came down to 7.7% with 5th year students. Previous research has reported a prevalence of suicidal ideation in medical students ranges from 9-48% (Kosik et al 2017). Many factors have been reported to contribute in the suicidal ideation including specific behavioural and personal characteristics, coexisting mental health problems, susceptibility to heavy curricular burdens, decreased life satisfaction and all of them together may lead to burnout, anxiety and depression (Kosik et al 2017).…”
Section: Association Of Mental Health Status With Demographic Variablesmentioning
confidence: 99%
“…Previous research has reported a prevalence of suicidal ideation in medical students ranges from 9-48% (Kosik et al 2017). Many factors have been reported to contribute in the suicidal ideation including specific behavioural and personal characteristics, coexisting mental health problems, susceptibility to heavy curricular burdens, decreased life satisfaction and all of them together may lead to burnout, anxiety and depression (Kosik et al 2017). Depression is particularly reported as a key risk factor responsible behind suicidal ideation, which was also higher in our study.…”
Section: Association Of Mental Health Status With Demographic Variablesmentioning
confidence: 99%